Implementasi Penguatan Profil Pancasila Berbasis Ethno-Edutaiment untuk Meningkatkan Karakter Mandiri dan Bergotong Royong Peserta Didik Sekolah Dasar - Febrilia, Yeyen; Sulistiawati, Anjar (PGSD STKIP PGRI Pacitan, 2023)
Research on strengthening the profile of Pancasila aims-describes the implementation of a project to strengthen the profile of Pancasila students based on ethnic education to improve the independent and cooperative character of elementary school students. The research method uses a qualitative description with the research object being class I SD Negeri Trayu. Methods of data collection by observing, interviewing, and documentation. Data analysis with selecting, focusing, and simplifying data according to the research focus (data condensation), presenting data (data display), and concluding (conclusion drawing/verification). The results of the research are that the implementation of strengthening Pancasila based on ethno-edutainment to improve the independent character and cooperation of elementary school students is carried out in four stages, namely stages of introduction, contextual, action, and reflection as well as follow-up based on ethno-edutainment. This encourages students to be able according to expectations to act independently, work together on, and being able to preserve Indonesian culture specifically in the form of special foods from Kulon Progo Regency.